Core-modified N-confused pentaphyrin variants with adaptive (anti)aromaticity - Jana, Manik; Velmurugan, Gunasekaran; Sahoo, Sumit; Comba, Peter; Rath, Harapriya (Organic chemistry frontiers, 2025)
The retrosynthetic design and syntheses of three unprecedented core-modified N-confused pentaphyrins (sapphyrins) possessing an E-ethylene bithiophene moiety with tunable Hückel (anti)aromaticity are reported. Solution-state spectroscopic analyses reveal the sustained E-conformation for the ethylene moiety. All three N-confused pentaphyrins exhibited vis-NIR absorption. All possible stereoisomers of the S2N3 hybrid N-confused pentaphyrins 14-16 have been unravelled via thorough DFT studies. DFT studies support the Hückel π aromaticity of pentaphyrins 14 and 16 but π-antiaromaticity for 15.